The creative process behind Dialogismos I: theoretical and technical considerations - Bernardes, Gilberto (2019)
This paper examines the aesthetic dimension and the technical realization of Dialogismos I, a piece for saxophone alto and electronics by the composer Nuno Peixoto de Pinho. The conceptual basis of the work relies on the notion of ‘intertextuality’ coined by the Bulgarian-French philosopher and literary critic Julia Kristeva, which was somehow transposed to the music domain by J. Peter Burkholder under the concept ‘musical borrowing’. The compositional problems raised by applying an intertextual musical thinking as a key driver of the composition were solved using two different approaches. The first approach was the manual selection of elements from several music works with different granularities to devise the overall structure of the work and to create the saxophone score. The second approach was applied to the realization of the electronic part and relied on concatenative sound synthesis as an algorithmic computer assisted composition method and a real-time synthesis technique.